Cloud Computing : 5th International Conference, CloudComp 2014, Guilin, China, October 19-21, 2014, Revised Selected Papers - Leung, Victor C.M.; Lai, Roy Xiaorong; Chen, Min.; Wan, Jiafu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post conference proceedings of the 5th International Conference on Cloud Computing, CloudComp 2014, held in Guilin, China, in October 2014. The 25 revised full papers were carefully reviewed and selected from 72 submissions and cover topics such as mobile cloud computing, services, applications, IoT on cloud, architectures and big data, cloud-assisted pervasive computing and services, management and virtualization for cloud, cloud security.
A Hybrid Remote Rendering Approach for Graphic Applications on Cloud Computing -- A Policy-based Application Service Management in Mobile Cloud Broker -- Personalized Video Recommendations with Both Historical and New Items -- A VM Reservation-based Cloud Service Broker and Its Performance Evaluation -- Virtualizing IMS Core and its Performance Analysis -- VM3: Virtual Machine Multicast Migration Based on Comprehensive Load Forecasting -- A Phased Workflow Scheduling Scheme with Task Division Policy in Cloud Broker -- An Efficient Data Extracting Method Based on Hadoop -- Based Big Data Analysis of Fraud Detection for Online Transaction Orders -- Question Classification based on Hadoop Platform -- A Dynamic and Static Combined Replication Management Mechanism Based on Frequency Adaptive -- A distributed business process collaboration architecture based on entropy in cloud computing -- DSBAF: Running My Web Services in your WS Environment -- Cloud-based Iterative RFID Tag Search Protocol Using Bloom Filters -- Design and Optimizations of The MD5 Crypt Cracking Algorithm Based on CUDA -- A Model of Cloud Computing Federation Based on Complex Network Theory -- The Implementation of IKEV2 For IPSec.
Keywords: Computer Communication Networks; Computer system performance; Software engineering; Computer Communication Networks; System Performance and Evaluation; Software Engineering; Information Systems Applications (incl. Internet).